초미세수술 로봇의 안정적인 원격조작을 위한 제어시스템 설계 - 김건욱; 델가도 라이마리우스; 인용석 (한국로봇학회, 2024)
In this study, we developed control system for stable teleoperation of supermicrosurgical robot platform. The supermicrosurgical robot platform is designed to perform precise anastomosis with micro vessels ranging from 0.3 mm to 0.7 mm. The robotic assistance could help more precise manipulation then manual surgery with the help of motion scaling and tremor filtering. However, since the robotic system could cause several vulnerabilities, control system for stable teleoperation should be preceded. Therefore, we first designed control system including inverse kinematics solver, clutch error interpolator and finite state machine. The inverse kinematics solver was designed to minimized inertial motion of the manipulator and tested by applying orientational motion. To make robot slowly converges to the leader’s orientation when orientational error was occurred during clutch, the SLERP was used to interpolate the error. Since synchronized behavior of two manipulators and independent behavior of manipulator both exist, two layered finite state machines were designed. Finally, the control system was evaluated by experiment and showed intended behavior, while maintaining low pose error.